ANALISIS NILAI HASIL TERHADAP PENGENDALIAN MANAJEMEN WAKTU PADA PROYEK PEMBANGUNAN GEDUNG MAPOLRES DEMAK LANJUTAN (STUDI KASUS : PEMBANGUNAN GEDUNG MAPOLRES DEMAK LANJUTAN) - Shanty Andriani Novita; Agung Sutarto (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Looking at the total level of rapid development of construction work, which is relatively fast, it becomes a challenge for the construction world. This is followed by the development of a very diverse method of various construction implementations applied in the process. In every construction project implementation, the main factor that makes the project successful or not is in terms of both time and cost. This research uses quantitative descriptive analysis research. In this descriptive analysis, which was carried out at the Mapolres Mapolres Advanced Building Project, the aim was to determine the time performance and find solutions to problems that existed in the implementation of this project. On the schedule variance graph (SV), the implementation of this project is all positive. Shows that this positive value is that the implementation of the work has accelerated or has not experienced delays, and the performance of the project implementation is better and faster following the initial planning. The value of the schedule performance index (SPI) on the overall implementation of this project from the 8th week to the 11th week shows a value of more than one (>1), so the project is completed faster than what has been planned.